Morbid obesity and type 2 diabetes alter intestinal fatty acid uptake and blood flow - Koffert Jukka; Ståhle Mia; Karlsson Henry; Iozzo Patricia; Salminen Paulina; Roivainen Anne; Nuutila Pirjo (Blackwell Publishing Ltd, 2025)
Aims: Bariatric surgery is the most effective treatment to tackle morbid obesity and type 2 diabetes, but the mechanisms of action are still unclear. The objective of this study was to investigate the effects of bariatric surgery on intestinal fatty acid (FA) uptake and blood flow. Materials and Methods: We recruited 27 morbidly obese subjects, of whom 10 had type 2 diabetes and 15 were healthy age-matched controls. Intestinal blood flow and fatty acid uptake from circulation were measured during fasting state using positron emission tomography (PET). Obese subjects were re-studied 6 months after bariatric surgery. The mucosal location of intestinal FA retention was verified in insulin resistant mice with autoradiography. Results: Compared to lean subjects, morbidly obese subjects had higher duodenal and jejunal FA uptake (P < .001) but similar intestinal blood flow (NS). Within 6 months after bariatric surgery, obese subjects had lost 24% of their weight and 7/10 diabetic subjects were in remission. Jejunal FA uptake was further increased (P < .03). Conversely, bariatric surgery provoked a decrease in jejunal blood flow (P < .05) while duodenal blood flow was preserved. Animal studies showed that FAs were taken up into enterocytes, for the most part, but were also transferred, in part, into the lumen. Conclusions: In the obese, the small intestine actively takes up FAs from circulation and FA uptake remains higher than in controls post-operatively. Intestinal blood flow was not enhanced before or after bariatric surgery, suggesting that enhanced intestinal FA metabolism is not driven by intestinal perfusion.